Policy Strategy of Rural Agribusiness Development Program for Agricultural Sharia Micro Economic Development - Zaenafi Ariani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
This research was conducted in the Combined Farmer Group (Gapoktan) West Sumbawa Regency. A common problem for farmers, not having good access to financing institutions, making it difficult to obtain credit or financing of agricultural businesses, such as people's business credit (KUR) from banks. This research is important to know the policy strategy of rural agribusiness development programs in the region, as well as the obstacles faced. The qualitative descriptive method aims to describe, summarize various conditions, situations, or phenomena of the social reality of the society that become the object of research, and try to draw that reality to the surface as a characteristic, character, nature, model, sign or description of a particular condition, situation, or phenomenon. The results showed that the policy strategy of rural agribusiness development program in the development of agricultural-based sharia microeconomics in West Sumbawa Regency was carried out to support the success of agricultural development. The government through the Minister of Agriculture of the Republic of Indonesia provided Direct Assistance to the Rural Agribusiness Development Community (BLM-PUAP) which was rolled out to the Combined Farmer Groups (Gapoktan) in each village.